MAQASID AL-SYARIAH MENURUT AL-GHAZALI DAN IBNU QOYYIM AL-JAUZIYAH - Paryadi Paryadi; Nashirul Haq (Cross-border, 2020)
Islam is a religion which is shalihun likulli zamanin makanin (always pious and develops in harmony in every era). Maqasid al-syariah is the initial gate that must be passed so that Islam may exist throughout the ages and everywhere. Maqasid al-syariah is a way to contextualize Islamic teachings in a scope surrounding Muslims. Then with maqasid al-syariah it is also able to provide solutions for any problems that may arise in the midst of the Muslim people. This qualitative research describes the differences and similarities of the theory of maqasid al-syariah of Imam al Ghazali and Ibnu Qoyyim al Jauziyah. Two different age mujtahids but have the ability to formulate the maqasid al-syariah